(untitled) (Research, Society and Development, 2021)
Scientometric indicators are useful for measuring academic productivity and its temporo-spatial impact. The aim of this study was to carry out a retrospective survey on Brazilian dental research with biomaterials for guided bone regeneration. Original thematic abstracts were retrieved from the SBPqO annals of the last four decades, making a sample of 1310 works, distributed in the categories of application, origin and composition of the biomaterial, type of study, regionality and financing. The amount of research has grown significantly from the 1990s and remained stable until the 2010s. The prevalence of in vivo research compared to clinical, structural, and in vitro studies was evident and the decrease other forms of application alternated with the increase in bone graft, membrane, and blood derivative. The autogenous origin was the largest in the 1980s, xenogeneic in the 1990s and 2000s and alloplastic in the 2010s. Although composites were more prevalent throughout the study period, from the 1990s polymers were more frequent than ceramics and bio-glass. The Southeast region has led research and financing over all the analyzed decades, even though the South, Northeast and Center-West regions have grown significantly in the theme and the North region has no production. The scoping study of biomaterials for guided bone regeneration indicates its gradual technical-scientific evolution and reinforces its historical relevance for Brazilian dental research.